Ekosistemski pristop za razumevanje prsti v geografiji - Vovk Korže, Ana (Revija za geografijo, 2015)
In International soil year of 2015, there are different activities going on to raise awarness about the importance of soils in the ecosystem. Soil for a long time now does not have only a cultivation role, but performs a lot of other roles, from water retention, water cleaning, humification process etc. That is why we showed in contribution, on an example of Dravinjske gorice, the importance of knowing the ecosytem role of soil. First of all, it is required to recognize different types of soils on the field and for a more precise knowledge of the soil it is necessary to perform analyzes of specific soil characteristics. To obtain the ecosystem insight into soil spread, we determine the biotopes, these are communities of soil. They consist of terrain data, gradient, altitude, exposition and vegetation spread. Additional information is related to the water balance in the soil and the water retention capacity of the soil. The ecosytem view on soil, at an early stage helps us to understand the sensitivity of the soil and therefore is recognized as a synthetic approach to soil protection.
Keywords: biotopi; ekosistemi; prst (pedologija); tla